Dual fuel maritime energy systems: speed models and analysis - Tan, Roy Ee Aun (Nanyang Technological University, 2022)
The research work in this thesis consists of two major parts. Firstly, to extend academic literature on bunkering for liner shipping with the application of dual fuel engines in providing fuel flexibility. Secondly, to analyze speed optimization and speed reduction models for liner shipping in a flexible dual fuel context with regards to the current ongoing speed limit debate at the International Maritime Organization. The focus is on the interplay of an average speed limit on the optimal speeds, carbon intensity and emissions in conjunction with fleet deployment.